Semiotics in John Edmond’s “The Last Word in Rhodesian” Song - Firmansyah Gani; Herlyna; Sri Marleni (The Doctoral Studies Program of Linguistics of Udayana University, 2024)
The exploration of literature transcends the boundaries of written texts, encompassing a diverse array of expressions, including spoken or sung compositions like song lyrics. While on the surface, songs may seem to convey straightforward messages, beneath it lies a labyrinth of symbols and nuances that beckon listeners to interpret. This interpretive process demands a nuanced understanding and a willingness to explore the depths of lyrical expression. This research aims to unravel the significance of each letter in the word